Moralność społeczna młodych ludzi w Anglii i Walii - Kay, William (Horyzonty Wychowania, 2017)
Five factors or agencies leading to the formation of social orpersonal morality in young people are identified. These arechurches, schools, families, communities and the similar impactsof militarisation and industrialisation. The influence of these agenciesor factors are surveyed in relation to Britain in the 19th and20th centuries. There is a discernible weakening of each influenceapart from that of schools but, even here, the government’s mainconcern is not with moral education.